Endurance Performance during Severe-Intensity Intermittent Cycling: Effect of Exercise Duration and Recovery Type - Barbosa, Luis F. [UNESP]; Denadai, Benedito S. [UNESP]; Greco, Camila C. [UNESP] (Frontiers Media Sa, 2016)
Slow component of oxygen uptake (VO2SC) kinetics and maximal oxygen uptake (VO(2)max) attainment seem to influence endurance performance during constant-work rate exercise (CWR) performed within the severe intensity domain. In this study, it was hypothesized that delaying the attainment of VO(2)max by reducing the rates at which VO2 increases with time (VO2SC kinetics) would improve the endurance performance during severe-intensity intermittent exercise performed with different work:recovery duration and recovery type in active individuals. After the estimation of the parameters of the VO2SC kinetics during CWR exercise, 18 males were divided into two groups (Passive and Active recovery) and performed at different days, two intermittent exercises to exhaustion (at 95% IVO(2)max, with work: recovery ratio of 2:1) with the duration of the repetitions calculated from the onset of the exercise to the beginning of the VO2SC (Short) or to the half duration of the VO2SC (Long). The active recovery was performed at 50% IVO(2)max. The endurance performance during intermittent exercises for the Passive (Short = 1523 +/- 411; Long = 984 +/- 260 s) and Active (Short = 902 +/- 239; Long = 886 +/- 254 s) groups was improved compared with CWR condition (Passive = 540 +/- 116; Active = 489 +/- 84 s). For Passive group, the endurance performance was significantly higher for Short than Long condition. However, no significant difference between Short and Long conditions was found for Active group. Additionally, the endurance performance during Short condition was higher for Passive than Active group. The VO2SC kinetics was significantly increased for CWR (Passive = 0.16 +/- 0.04; Active = 0.16 +/- 0.04 L.min(-2)) compared with Short (Passive = 0.01 +/- 0.01; Active = 0.03 +/- 0.04 L.min(-2)) and Long (Passive=0.02 +/- 0.01; Active = 0.01 +/- 0.01 L.min(-2)) intermittent exercise conditions. No significant difference was found among the intermittent exercises. It can be concluded that the endurance performance is negatively influenced by active recovery only during shorter high-intensity intermittent exercise. Moreover, the improvement in endurance performance seems not be explained by differences in the VO2SC kinetics, since its values were similar among all intermittent exercise conditions.
Keywords: aerobic; oxygen uptake; passive; active; exercise tolerance